Effects of Bans on Prostitution on Prevalence of Induced Abortions - Kobayashi, Takahide; Kobayashi, Hiroyuki (The Journal of Medicine, Law & Public Health, 2025)
Background: Prostitutes are at high risk of unintended pregnancy, and induced abortions are widely practised among this cohort. Aims: This study examined the effects of prostitution bans on the prevalence of induced abortions. We focused particularly on the bans on juvenile prostitution, which were introduced by 32 states of Japan between 1975 and 1998. Methods: This was a cross-sectional study employing event-study analyses and a difference-in-difference-in-differences methodology. We compared the changes in numbers of induced abortions before and after the bans were introduced, among women under 20 years of age and among those aged 20―24 years, over states. Results: The number of induced abortions among women under 20 years of age increased after the juvenile prostitution bans were implemented. In the fifth year of implementation, the number increased by 56.79 percentage points (p < 0.001) compared with the previous year. Conclusion: The number of induced abortions among adolescents increased after juvenile prostitution was banned. As to its mechanism, the outcomes of our additional identification suggest that former juvenile prostitutes who retired due to the bans contributed to the increase.